Synadenium umbellatum and the Ehrlich's solid tumor treatment: Assessment of inflammatory regulators (transforming growth factor protein-β1 and tumor necrosis factor-α) gene expression, hepatotoxicity and myelotoxicity. Issue 1 (January 2019) - da Silva, Emerson B.; Chagas, Camila S.; Fonseca, Alexandre L. A.; Alves, Beatriz da C. A.; Bagatin, Izilda; Perazzo, Fábio F.; Rosa, Paulo; Feder, David; Fonseca, Fernando Luiz A.
Abstract: Introduction: Studies have been attributed to cancer treatment, including the potential of several plants with putative anticancer activity. Among these is "Cola-note" ( Synadenium umbellatum ). Methods: We evaluated the effects of macerated S umbellatum at a concentration of 10 mg/kg in Bagg albino strain c mice and its myelotoxic, hepatotoxic, and antitumor activity as well as the expression of inflammatory genes (TGF-β1 and TNF-α). Cells from Ehrlich tumor were implanted in the dorsolateral region of 8 mice of the Bagg albino strain c mice; these animals were divided into control (treated with NaCl 0.9%) and treatment group (treated with macerated Cola-Nota 10 mg/kg). Results: Treatment group animals showed no hepatotoxicity, but a potential myelotoxicity. The results suggest that treatment with Cola-Note macerate causes a decrease in expression of TNF-α and an increased expression of TGF-β1. Discussion: The S umbellatum (10 mg/kg) is shown to be effective in reducing the concentration of neoplastic cachexia, but there was no antitumor activity.